Formulasi Dan Karakteristik Fisik Sediaan Plester Hidrogel Ekstrak Daun Ciplukan (Physalis angulata L.) Dan Batang Kayu Manis (Cinnamomum burmannii) - Ria Hanistya; Karima Samlan (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Diabetes mellitus is a degenerative disease caused by the damage of beta pancreatic cells. This caused many complication such as diabetic ulcer which left untreated can cause an open wound hard to heal thereby reducing the quality of life. Treatment of diabetic ulcer despite using antidiabetic also using an antibiotic therapy like Mupirocin. In its development, the use of natural ingredients is known to be used as adjuvant therapy for diabetic ulcer such as Ciplukan leaves and Kayu Manis bark. Both of the plant contain phytochemical compound like sinamaldehid, tannin, polyphenol and flavonoid which can work as wound healer. To increase its efficacy then Ciplukan leaves and Kayu Manis bark were formulated as hydrogel patch. Hydrogel patch are known has advantages like better penetration, hygienic and easy to administered Ciplukan (Physalis angulata L.) leaves and Kayu Manis (Cinnamomum burmannii) Bark extracted with maceration technique. The extracts then made into matrix type hydrogel patch with 10% HPMC and 5% PVA as backing patch. The backing patch and extract then placed on a square cast and dried under room temperature for 24 hours. The hydrogel patch then evaluated for physical characteristic including organoleptic aspect, weight uniformity, moisture content and pH. The results showed that Ciplukan leaves and Kayu Manis Bark hydrogel patch have a semi solid consistency, transparent greenish color and distinctive smell. The average pH is 5,5 and have average weight around 1,18 grams. The moisture contens of hydrogel patch is 2,42%. The Ciplukan leaves and Kayu Manis bark is able to formulated into hydrogel patch. The hydrogel patch is showing good appearance and having good properties as topical dosage form. The pH of the hydrogel patch is suitable with pH of the skin and have no intention to irritate the skin. Hydrogel patch also giving a cooling sensations in wound area thus increase patients convenience and acceptability.  Keywords: Diabetes mellitus, extract, drug delivery system, hydrogel patch, adjuvant therapy